Mussel communities in the middle tide zone of rocky shore from Lima - Paredes, Carlos (1980)
Thirty-four samples of mussel assemblages were studied in the rocky mid-littoral zone at 10°45'38"S - 12°57'39"S, in the department of Lima, Peru. Such samples were taken periodically, between June and November, 1972. Using the biological index method, two kinds of communities were determined for the area: community of Perumytilus purpuratus (Lamarck, 1819), in the mid-horizon of the mid-littoral zone and community of Semimytilus algosus (Gould, 1850), in the lower horizon of the mid-littoral zone.